Socioeconomic Disparities in the Prevalence of Blepharoptosis in the South Korean Adult Population Based on a Nationwide Cross-Sectional Study. - Eun Young Rha; Kyungdo Han; Yongkyu Park; Gyeol Yoo (PLoS ONE, 2016)
We investigated the association between socioeconomic status (SES) and the prevalence of blepharoptosis in a representative South Korean population.This cross-sectional study was based on data obtained in the Korea National Health and Nutrition Examination Survey from 2010 to 2012. In total, 17,178 Korean adults (7,261 men and 9,917 women) aged 19 years or older were enrolled. Blepharoptosis was defined as a marginal reflex distance 1 (MDR 1) lower than 2 mm. Household income and education level were used as indicators of SES. Univariate and multiple logistic regression analyses were conducted to analyze the relationship between SES and the prevalence of blepharoptosis.Household income was inversely associated with the prevalence of blepharoptosis in women [adjusted odds ratio (aOR) and corresponding 95% confidence interval (95% CI) was 1.894 (1.336, 2.685)], and educational level was inversely associated with blepharoptosis in both men and women [aORs and 95% CIs were 1.572 (1.113, 2.219) and 1.973 (1.153, 3.376), respectively]. After adjusting for household income and educational level, low SES was associated with a high prevalence of blepharoptosis in women only.Socioeconomic disparities in the prevalence of blepharoptosis were found among women. Indeed, future research using a prospective design to determine the causal relationship between SES and blepharoptosis may identify SES as a risk factor for this condition.